Meminimalisir fenomena flexing melalui kaedah ushul fiqh: pembatasan penggunaan harta berbasis maslahat - Putri, Nawangsasi Kusuma (Maliki Interdisciplinary Journal, 2025)
Flexing, which shows off wealth or excess material, is rampant on social media, especially in the younger generation, and has negative social and psychological impacts. This study aims to examine the phenomenon of flexing from the perspective of Ushul Fiqh with a maslahat approach to formulate excessive use of property. The method used is qualitative, descriptive-analytical, with literature studies from classical and contemporary fiqh literature, and analyzing empirical phenomena that develop in society. The results of the survey show that Ushul Fiqh methods such as tazhir (preventive punishment), sadd adh-dhari’ah (closing the path of harm), and jalb al-mashalih (seeking benefit) can be a normative and practical basis for limiting flexing behavior. The implementation of this method needs to be supported by social policies, strengthening religious value education, and social media regulations to create a harmonious and responsible society in the use of property. This study provides an academic contribution and a practical solution based on Islamic values to overcome the negative impact of flexing for the benefit of the people.